Mitigating emotional exhaustion and disability claims: the roles of health and well-being climate and supervisor support - Marie-Ève Beauchamp Legault; Denis Chênevert; Sari Mansour (Frontiers in Organizational Psychology)
IntroductionThis study examines the effect of the Health and Well-being Climate (HWC) and the moderating role of supervisor support on employees' emotional exhaustion and insurance claims, grounded in the Conservation of Resources theory.MethodsQuantitative data were collected from 661 employees across 17 organizations in Canada, and group insurance claims data for these employees were also analyzed. Structural equation modeling was conducted using IBM SPSS AMOS 28.0 to test all hypotheses.FindingsThe results indicate that a positive perception of the HWC among employees reduces both emotional exhaustion and the number of disability claims. Furthermore, supervisor support moderates the relationship between HWC and emotional exhaustion. High levels of emotional exhaustion and disability claims from employees can result in significant direct and indirect costs for employers. This study aims to provide organizations, managers, and practitioners with insights into effective strategies for mitigating these costs.